The relationship between health literacy and quality of life among diabetes mellitus patients in the working area of Darul Imarah Subdistrict Health Center - Isnani, Ayu; Hermansyah, Hermansyah; Maidar, Maidar; Saputra, Irwan; Abdullah, Asnawi; Rani, Hafnidar Ar (Science Midwifery, 2024)
The study aimed to examine the relationship between health literacy and the quality of life of Diabetes Mellitus (DM) patients in the Darul Imarah Sub-District Health Center, Aceh Besar District. Using an analytical observational design with a cross-sectional approach, the study included 1,125 DM patients, with 100 individuals selected as research samples. Data analysis involved univariate, bivariate, and multivariate analysis using logistic regression. The findings revealed that a majority of DM patients in the working area of the health center experienced poor quality of life (82%). Additionally, there was a significant relationship between health literacy and the quality of life of DM patients (OR=8.34; 95% CI=1.05-66.05; p=0.044). Confounding assessment identified socioeconomic status, family history of DM, access to information, and low physical activity as factors influencing the quality of life of DM patients. The multivariate analysis highlighted socioeconomic status as the most dominant factor (OR=25.43; 95% CI=2.24-288.44; p=0.009). In conclusion, DM patients in the Darul Imarah Sub-District, Aceh Besar Regency, generally have poor quality of life, with health literacy, socioeconomic factors, descent, information access, and physical activity playing significant roles in influencing it.